Small Non-coding RNAs: Do They Encode Answers for Controlling SARS-CoV-2 in the Future? - Bhattacharyya, Pallabi; Biswas, Subhas C. (Frontiers in Microbiology, 2020)
SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) is a novel coronavirus responsible for the current COVID-19 (coronavirus disease 2019) pandemic, which has hit the world since December 2019. It has spread to about 216 countries worldwide, affecting more than 21.7 million people so far. Although clinical trials of a number of promising antiviral drugs and vaccines against COVID-19 are underway, it is hard to predict how successful these drug- or vaccine-based therapeutics are eventually going to be in combating COVID-19 because most of such therapeutic strategies have failed against human coronaviruses such as SARS-CoV and MERS-CoV (Middle East respiratory syndrome coronavirus) responsible for similar pandemics in the past. In that context, we would like to bring to scientific attention another group of endogenous regulatory molecules, the small non-coding RNAs, especially the microRNAs, which are found to regulate critical cellular pathways in a number of disease conditions, including RNA viral infections. This review will focus on understanding the effect of altered microRNA expression during coronavirus-mediated infections and how it may provide clues for further exploring the pathogenesis of SARS-CoV-2, with a view of developing RNAi-based therapeutics and biomarkers against COVID-19.